The pharmacology of memory. - Iversen, S (1998)
Neurotransmitters play a critical role in the brain circuits involved in various aspects of memory. The importance of acetylcholine is illustrated by the psychopathology of Alzheimer's disease. Cholinergic replacement therapy is now available for treating the cognitive decline associated with this form of degenerative disease. Dopamine in the prefrontal cortex also contributes to information storage, particularly working memory. In both cases efforts have been made to identify the receptor subtype involved and such information is essential if pharmacologically specific drugs are to be developed for cognitive enhancement.